Acute airway compromise after recombinant human TSH administration: A case report and review of the literature. (10th December 2019) - Dowling, Eric; Kasperbauer, Jan; Morris, John; Bayan, Semirra
Abstract : Radioiodine ablation is a commonly utilized treatment for differentiated thyroid carcinoma. Uptake of radioiodine can be enhanced by pretreatment with thyroid hormone withdrawal or administration of recombinant human thyroid‐stimulating hormone (rhTSH). rhTSH is generally well‐tolerated with minimal adverse effects. However, in patients with extensive tumor burden in confined anatomic spaces, rapid enlargement of normal or neoplastic thyroid tissue secondary to rhTSH administration can result in significant compressive effects. In this report, we describe a case of rapid airway deterioration requiring intubation in a patient with involvement of the thyroid cartilage by papillary thyroid carcinoma. Laryngoscope, 122:0000–0000, 2019 Laryngoscope, 130:2725–2727, 2020